A comprehensive characterisation of safflower oil for its potential applications as a bioactive food ingredient - A review. (August 2017) - Khalid, Nauman; Khan, Rao Sanaullah; Hussain, M. Iftikhar; Farooq, Muhammad; Ahmad, Asif; Ahmed, Iftikhar
Abstract: Background: Safflower is a multiple purpose crop generally grown for oil production. The safflower oil is considered to be a better oil since it contains higher amount of oleic and linoleic acids than other oil seed crops. Safflower oil has numerous applications in food, cosmetics, pharmaceutical and feed industry. An added advantage of safflower oil is lower cost of production thus can become an alternate option for those who cannot afford to buy olive and other functional oils. Scope and approach: This manuscript provides a comprehensive review on critical aspects of pharmacological and nutritional applications of safflower oil. A higher antioxidant activity renders better stability of safflower seed oil over extended storage period. Moreover, a higher content of omega six fatty acids makes it a healthier choice for consumption especially where olive oil being the only but costly choice. There has been a surge in developing innovative and efficient methods to extract safflower oil including super critical fluid and enzymatic extraction techniques. Key findings and conclusions: A higher stability index makes it possible to encapsulate safflower oil or used it as a carrier in bioactive functional ingredient delivery systems. The functional properties of safflower oil can be used to treat skin infections, bone related disorders, menopause and atherosclerosis. Composition and distribution of phenolic contents of safflower oil has not been explored to its full potential. There is a need to conduct exclusive research on exploring the role of phenolic compounds in food and pharma industrial applications. Highlights: Safflower oil have been reviewed for nutraceutical applications. Good stability index allows encapsulation of safflower oil in functional foods. Recently extraction techniques of safflower oil have been reviewed. Summary of recent findings related to bone health is reviewed. Applications of safflower oil towards functional foods development is reviewed.